2007
DOI: 10.1562/0031-8655(2002)0750561baoces2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Binding Affinities of Commonly Employed Sensitizers of Viral Inactivation¶

Abstract: Methylene blue (MB), riboflavin (RB) and psoralen sensitizers (4′ aminomethyl‐4,5′,8‐trimethylpsoralen [AMT] and derivatives) are under study as sensitizers of viral inactivation of blood products such as plasma proteins, platelets and red cells, all of which lack genomic nucleic acid. To predict where these sensitizers accumulate in viruses and in cells, their relative affinities for calf thymus DNA, neutral and negatively charged phospholipids and albumin were determined by dialysis. MB has a strong affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Furthermore, all photosensitizers produce reactive oxygen species (ROS), and these are by no means specific in their chemistry with the surrounding milieu. Moreover, photosensitizers not only partition to nucleic acids , but also to other biomolecules where reaction can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, all photosensitizers produce reactive oxygen species (ROS), and these are by no means specific in their chemistry with the surrounding milieu. Moreover, photosensitizers not only partition to nucleic acids , but also to other biomolecules where reaction can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Second, overall cell damage is generated by reactive oxygen species, which are formed between riboflavin after UV illumination and oxygen in the PLT transfusion product. Finally, riboflavin intercalates into nucleic acid strands and oxidizes guanine bases upon illumination resulting in more damage to the cells 7‐9…”
mentioning
confidence: 99%
“…Several studies reported some vitamins as virus inactivators, e.g. riboflavin, present in our vitamins cocktail, was shown to selectively induce damage only to nucleic acids (Dardare and Platz, 2002) and probably this may explain the significant decrease on cell specific productivity, since AdV DNA damage might be occurring during AdV replication.…”
Section: Resultsmentioning
confidence: 94%